Do Silicon-Based Li-Ion Batteries Require a Time-Consuming Solid Electrolyte Interphase Formation Process? - Sheng S. Zhang (Batteries)
The solid electrolyte interphase (SEI) is a crucial component for ensuring the safe and long-term cycling of graphite-based Li-ion batteries. Traditionally, SEI formation requires a low current rate (0.05C–0.1C) and a moderate temperature (25–45 °C), and the same process has been widely applied in the manufacturing of silicon-based Li-ion batteries. However, silicon stores Li+ ions through different mechanisms than graphite, raising the question of whether such a time-consuming SEI formation process is necessary. In this work, carbon-coated SiOx is selected as a representative silicon material, and both Li/SiOx half-cells and SiOx/LiNi0.8Co0.1Mn0.1O2 (NCM811) full cells are assembled and cycled at varying current rates for the first 10 cycles, followed by identical cycling conditions for the subsequent cycles. The results show that the initial current rate has a minimal impact on the long-term cycling stability of both SiOx-based Li metal half-cells and Li-ion cells. Notably, Li-ion cells formed at higher current rates exhibit lower overall impedance than those formed at lower current rates, consequently demonstrating better rate capability. These findings suggest that the time-consuming SEI formation process may not be necessary for the manufacturing of silicon-based Li-ion batteries, potentially simplifying production and reducing processing time.